New insight into the importance of formulation variables on parenteral growth hormone preparations: potential effect on the injection-site pain - Taghizadeh, Bita; Jaafari, Mahmoud Reza; Zarghami, Nosratollah (Frontiers in Endocrinology, 2022)
Reducing injection-site pain (ISP) in patients with chronic conditions such as growth hormone deficiency is a valuable strategy to improve patient compliance and therapeutic efficiency. Thus understanding different aspects of pain induction following subcutaneous injection of biotherapeutics and identifying the responsible factors are vital. Here we have discussed the effects of formulation’s viscosity, concentration, osmolality, buffering agents, pH, and temperature as well as injection volume, dosing frequency, and different excipients on ISP following subcutaneous injection of commercially available recombinant human growth hormone products. Our literature review found limited available data on the effects of different components of parenteral rhGH products on ISP. This may be due to high cost associated with conducting various clinical trials to assess each excipient in the formulation or to determine the complex interactions of different components and its impact on ISP. Recently, conducting molecular dynamics simulation studies before formulation design has been recommended as an alternative and less-expensive approach. On the other hand, the observed inconsistencies in the available data is mainly due to different pain measurement approaches used in each study. Moreover, it is difficult to translate data obtained from animal studies to human subjects. Despite all these limitations, our investigation showed that components of parenteral rhGH products can significantly contribute to ISP. We suggest further investigation is required for development of long acting, buffer-free, preservative-free formulations. Besides, various excipients are currently being investigated for reducing ISP which can be used as alternatives for common buffers, surfactants or preservatives in designing future rhGH formulations.